Changes of cardiorespiratory response sensivity and fast kinetics after strenous training workloads in young versus adult kayakers - Mishchenko, V.; Kalinski, M.; Tomiak, T. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The cardiorespiratory (CRS) response sensitivity and fast kinetics is reduced transiently as a result of athletes` fatigue of strenuous training workloads (Mishchenko, Monogarov,1995). It was theorized that fatigue induced CRS responsiveness have to related to age difference and sports specific feature of endurance athletes. However, the possible difference in CRS response sensitivity and kinetics between young and adult endurance athletes were not elucidate. The aim of this study was to determine whether induced fatigue transient changes and time duration of carbon dioxide, hypoxia response sensitivity and fast kinetics could differentiate between young and adult elite kayakers. Methods Twenty two male highly endurance-training kayakers 17-29 yrs old were divided into two ages groups. Ten young athletes aged 17,3(0,1) yrs and twelve adult kayakers 24,5(0,3) yrs (VO2 max 64,5(1,3) and 64,9(1,1) respectively, p>0,05) participated in the same two very strenuous training session during one day. Before sessions and 13-15 and 37-39 hours after the last training workload CRS responses to carbon dioxide (ÄVE/ÄPACO2), iso-capnic hypoxia (ÄHR/ÄSaO2) (in morning standard rest, rebreathing method) as well fast kinetics (T50, transition from 25w) and CRS peaks response to specific ergometric cycle exercise (1,1 VO2 max) were measured (breath by breath, Oxycon Alfa). Age comparisons were made by using ANOVA with repeated measures and significance was set at ** p<0,05. Results The results showed that young athletes 13-15 hours after the last workload had significantly higher degree induced fatigue decrease of lung ventilation CO2-sensitivity ( 18,1±3,0 vs. -10,2±2,1 %, mean and SD, p<0.05), VE peak for 1,1 VO2 max (-6.9±1.0 vs. -3.9±0.6%, p<0.05), increasing of HR response to hypoxia (14,9±2,1 vs. 9,1±1,8%, p<0.05) and decrease of fast kinetics (T50) VO2 at 1,1 VO2 max constant-load (16,2±2,8 vs. 7,1±1,9%, p<0.05). Differences in degrees of VO2 peak decrease induced fatigue ( 3,9±0,5 vs. -3,1±0,4% in young and adult athletes, respectively) were un-valid (Fig.1). The hypo-kinetic features of CRS responses 13-15 hours after one day strenuous training session were observed in all athletes. But after 37-39 hours resting period there were no valid differences in CRS responsiveness compared to levels before training session in both groups except increasing hypoxia response sensitivity in the group of young athletes. Discussion/Conclusion We concluded that induced fatigue effects of one day strenuous training were linked with hypo-kinetic feature of CRS response. It was significantly related to ages differences of high performance endurance athletes 17-29 yrs. Such features were more expressed in young kayakers. The changes of athletes CRS response sensitivity and fast kinetics were expressed rather then change in peak response of VO2 and lung ventilation to physical exercise at 1,1 VO2 max. It presumably modify training effects of the next consecutive training session differently in the young and adult athletes. The material of kayakers in comparison with the same data of young rowers ( Mishchenko, Tomiak,Vinogradov,2003) shows the tendency of increasing in CRS response changes after strenuous training in kayakers. It may be related to peculiarities of CRS drive mechanism in arm exercise.